Genomic Context Analysis of de Novo STXBP1 Mutations Identifies Evidence of Splice Site DNA-Motif Associated Hotspots. Issue 4 (1st April 2018) - Uddin, Mohammed; Woodbury-Smith, Marc; Chan, Ada J S; Albanna, Ammar; Minassian, Berge; Boelman, Cyrus; Scherer, Stephen W
Abstract: Mutations within STXBP1 have been associated with a range of neurodevelopmental disorders implicating the pleotropic impact of this gene. Although the frequency of de novo mutations within STXBP1 for selective cohorts with early onset epileptic encephalopathy is more than 1%, there is no evidence for a hotspot within the gene. In this study, we analyzed the genomic context of de novo STXBP1 mutations to examine whether certain motifs indicated a greater risk of mutation. Through a comprehensive context analysis of 136 de novo /rare mutation (SNV/Indels) sites in this gene, strikingly 26.92% of all SNV mutations occurred within 5bp upstream or downstream of a 'GTA' motif ( P < 0.0005). This implies a genomic context modulated mutagenesis. Moreover, 51.85% (14 out of 27) of the 'GTA' mutations are splicing compared to 14.70% (20 out of 136) of all reported mutations within STXBP1 . We also noted that 11 of these 14 'GTA' associated mutations are de novo in origin. Our analysis provides strong evidence of DNA motif modulated mutagenesis for STXBP1 de novo splicing mutations.